The molecular sociology of the cell. - Robinson, C; Sali, A; Baumeister, W (2007)
Proteomic studies have yielded detailed lists of the proteins present in a cell. Comparatively little is known, however, about how these proteins interact and are spatially arranged within the 'functional modules' of the cell: that is, the 'molecular sociology' of the cell. This gap is now being bridged by using emerging experimental techniques, such as mass spectrometry of complexes and single-particle cryo-electron microscopy, to complement traditional biochemical and biophysical methods. With the development of integrative computational methods to exploit the data obtained, such hybrid approaches will uncover the molecular architectures, and perhaps even atomic models, of many protein complexes. With these structures in hand, researchers will be poised to use cryo-electron tomography to view protein complexes in action within cells, providing unprecedented insights into protein-interaction networks.